Revisiting Bucket Truck: Locally Engaged Public Intellectuals - Adrian M. Downey (Canadian Society for Studies in Education, 2019)
In this essay, the author argues that given current shifts in the axiological imperatives which inform research, local manifestations of the global political trend toward post-truth populism, and the saturation of the university in settler colonial, patriarchal, hegemonic ideology, there is a dire need for an alternative model of scholarly engagement-what the author calls locally engaged public intellectuals. Through the lyrics of Canadian rock band Bucket Truck, the author gestures toward the way local critiques can contextualize local issues and disrupt the post-truth narrativizing which often paints Indigenous and other marginalized groups as dissidents. Bucket Truck, the author argues, were an example of such locally engaged public intellectuals. The group thus deserves our consideration not just as a now defunct Canadian rock band, but as an example of local critique made accessible to affected communities.